MULTILATERAL DIPLOMACY AND SOFT POWER: UZBEKISTAN'S REGIONAL INITIATIVES IN CENTRAL ASIA - Nizomiddin Bahromovich Rajabboyev; Rakhmatulla Ibragimovich Nurimbetov (International Scientific and Current Research Conferences, 2025)
This article analyzes the role of international organizations—particularly the World Bank, the International Monetary Fund (IMF), and the United Nations (UN)—in shaping political reforms in Uzbekistan. The study examines how these organizations contribute to institutional transformation, policy development, and governance restructuring in the post-Soviet context. It explores how financial assistance, technical support, and policy dialogue provided by international actors promote Uzbekistan’s shift toward transparency, accountability, and the rule of law. The paper also evaluates the compatibility of international reform models with the local political dynamics and governance culture of Uzbekistan.